Improving Word Reading Literacy Through the Singing Method at UPTD SD Inpres Kolokoa - Mue, Maria Roswita; Fikri, Kanzul; Dopo, Ferdinandus Bate; Wewe, Melkior (SAINTIS Publishing, 2024)
This study aims to analyze the function of music as a means of improving children's reading literacy skills at UPTD SD Inpres Kolokoa. This research is a classroom action research with a spiral model from Kemmis and mc Tagart. The average assessment result in cycle 1 consisting of 10 students in the group reading words with the application of the singing method was 705 or 70.5%. However, in the first cycle, it is still classified as a criterion for reading enough words based on the assessment criteria by the researcher. Meanwhile, in cycle 2 consisting of 10 students who were in the group reading words with the application of the singing method was 895 or 89.5%, meaning there was an increase of 29.79%. In cycle II, reading ability is classified as a good criterion based on the assessment criteria by the researcher. Thus, music has proven to be effective in supporting the development of children's literacy in the elementary school environment.